1995
DOI: 10.3136/fsti9596t9798.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Tetrazolium Salt XTT with UHT-Treated Milk: Its Relationship with the Extent of Heat-Treatment and Storage Conditions.

Abstract: Agricu/ture, Kochi University, Monobe B-200, Nankoku Co., Ltd., 1-2l-3, Sakae-cho, Higashimurayama, Tokyo 783, Japa n 189, Japan UHT-treated milk reduced 3'-{1-L(phenylamino)-carbonylJ-3,1~tetrazolium}-bis(4hmethoxy-6-nitro)benzenesulfonic acid hydrate (XTT). The reducibility was caused by the Maillard reaction intermediate between milk protein and lactose. First, the assay procedure of the XTT reduction was optimized using the heated model solution containing casein and lactose and UHT-treated milk. When the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
15
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…This result showed that the ferricyanide-reducing substances might be stable unlike the XTT-reducing substance. In addition, we found that the HMF value of Milk C did not significantly change during its storage for 60 days at 5°C [11]. It was in accordance with the result of Fink and Kessler about HMF [13].…”
Section: Monitoring Of the Maillard Reaction Of Milk Using Xtt Assaysupporting
confidence: 79%
See 1 more Smart Citation
“…This result showed that the ferricyanide-reducing substances might be stable unlike the XTT-reducing substance. In addition, we found that the HMF value of Milk C did not significantly change during its storage for 60 days at 5°C [11]. It was in accordance with the result of Fink and Kessler about HMF [13].…”
Section: Monitoring Of the Maillard Reaction Of Milk Using Xtt Assaysupporting
confidence: 79%
“…We proposed an assay method for determining the ability of milk to reduce 3'-[1-[(phenylamino)-carbonyl]-3,4-tetrazolium]-bis(4-methoxy-6-nitro)benzensulfonic acid hydrate (XTT: Figure 1) as a method of evaluating the extent of the Maillard reaction [8][9][10][11]. The tetrazolium salt XTT is reduced to water-soluble formazan which is suitable for the spectrophotometric measurement.…”
Section: Monitoring Of the Maillard Reaction Of Milk Using Xtt Assaymentioning
confidence: 99%
“…We proposed an assay method for determining the ability of UHT-treated milk to reduce XTT (3¢-[1-(phenylamino)-carbonyl]-3,4-tetrazolium)-bis(4-methoxy-6-nitro)benzenesulfonic acid hydrate) as a method for evaluating the extent of the Maillard reaction (Ukeda et al, 1995(Ukeda et al, , 1996(Ukeda et al, and 1998. Compared with the conventional methods, the XTT assay is more rapid and convenient and is found to be applicable for estimating not only the extent of thermal treatment but also the storage conditions.…”
mentioning
confidence: 99%
“…Compared with the previously reported methods such as the quantification of lactulose (Geier & Klostermeyer,1 980), HMF (Keeney & Bassette,1 959) and furosine (Finot et al, 1981), the XTT reduction assay is a rapid and convenient method and is found to be applicable for estimating not only the extent of thermal treatment but also the storage conditions because the ability decreased dependent on the storage period and temperature (Ukeda et al, 1995). However, a drawback of the method was caused by the fact that the XTT used was a relatively expensive reagent.…”
mentioning
confidence: 99%
“…The authors have proposed an assay method for determining the ability of UHT-treated milk to reduce XTT as a method of evaluating the extent of the Maillard reaction (Ukeda et al, 1995). Compared with the previously reported methods such as the quantification of lactulose (Geier & Klostermeyer,1 980), HMF (Keeney & Bassette,1 959) and furosine (Finot et al, 1981), the XTT reduction assay is a rapid and convenient method and is found to be applicable for estimating not only the extent of thermal treatment but also the storage conditions because the ability decreased dependent on the storage period and temperature (Ukeda et al, 1995).…”
mentioning
confidence: 99%